Industrial training report: Universiti Kuala Lumpur (UniKL) MSI branch / Muhammad Akmal Khir Mat Khir - Mat Khir, Muhammad Akmal Khir (Universiti Teknologi MARA, Perlis, 2021)
This industrial training report is a mandatory task prepared on final year by a student of Bachelor of Business Administration Finance, Uitm Perlis. All students whoarequalified to undergo the industrial training must select an internship placement that suits the students’ criteria.My name is Muhammad Akmal Khir Bin Mat Khir, I wasqualified to undergo my industrial training at Universiti Kuala Lumpur (UniKL) MSI branch, and was placed under finance department. Throughout the learning process of my bachelor’s degree, I was exposed to variousstudies areas especially in finance and administration. I was required to chooseanorganization which is related to these areas of studies. This actually helps thestudents to apply the knowledge that we have obtained during our years of study. Auspiciously, UniKL MSI was the right place that has enabled me to apply most of the knowledge that I acquired from the mentioned areas. During the industrial training period, I was given a great guidance and enlightenment on administration tasks as well as office management skills. I will be suretoremember everything that had been taught and apply it in my future job if necessary. The industrial training starts from 1 st March 2021 until 13 th August 2021